Alginate hydrogel enriched with enamel matrix derivative to target osteogenic cell differentiation in TiO2 scaffolds. (12th March 2015) - Pullisaar, Helen; Verket, Anders; Szoke, Krisztina; Tiainen, Hanna; Haugen, Håvard J; Brinchmann, Jan E; Reseland, Janne E; Østrup, Esben
The purpose of bone tissue engineering is to employ scaffolds, cells, and growth factors to facilitate healing of bone defects. The aim of this study was to assess the viability and osteogenic differentiation of primary human osteoblasts and adipose tissue–derived mesenchymal stem cells from various donors on titanium dioxide (TiO2 ) scaffolds coated with an alginate hydrogel enriched with enamel matrix derivative. Cells were harvested for quantitative reverse transcription polymerase chain reaction on days 14 and 21, and medium was collected on days 2, 14, and 21 for protein analyses. Neither coating with alginate hydrogel nor alginate hydrogel enriched with enamel matrix derivative induced a cytotoxic response. Enamel matrix derivative–enriched alginate hydrogel significantly increased the expression of osteoblast markers COL1A1, TNFRSF11B, and BGLAP and secretion of osteopontin in human osteoblasts, whereas osteogenic differentiation of human adipose tissue–derived mesenchymal stem cells seemed unaffected by enamel matrix derivative. The alginate hydrogel coating procedure may have potential for local delivery of enamel matrix derivative and other stimulatory factors for use in bone tissue engineering.